Formation of the Concept of Measuring Compliance with Domestic Brands in four Dimensions According to Model 4-D (Economic journal of Lesya Ukrainka Volyn National University, 2016)
It was established that the majority of Ukrainian producers do not have time to modify their products to market requirements, positioning the brand are paying insufficient attention, leading to a sales decline are analyzed approach proposed by T. Guesde, who claims that «brand – differentiating the company code». The model 4-D (4 dimensional model brendyhnu), which includes four dimensions: functional, social, spiritual and mental. The results of research on the concept of matching models 4-D experience of interaction Ukrainian consumers some domestic brands. Described measurements that are prevalent in the studied national mark. Presented a study which showed that out of eleven Ukrainian brands studied only in two dimensions used all four models of 4-D. Found that in most used functional measurement (seven of eleven investigated marks). Concluded that the characteristics of the concept of branding in the domestic market determines the specificity Ukrainian consumer behavior.